Guideline for Life Quality Development of the Elderly in Khlong Kai Thuen Subdistrict, Khlong Hat District, Sa Kaeo Province through Elderly School Learning Activities - Chittabut, Pensri; Charoensangsuksri, Pimporn; Pitdon, Ritthaikarn; Khumhangsong, Chakrin; Tangpan, Chalini (Research and Development Journal Sisaket Rajabhat University, 2025)
This research aimed to study 1) the situation of aging society in Khlong Kai Thuen Subdistrict; 2) factors related to the development of the quality of life of the elderly and; 3) possible guidelines for improvements on the quality of life of the elderly through activities in the elderly school. This research was conducted using semi-structured interviews and surveys to collect data on the elderly’s quality of life. A total of 30 elderly participants were selected using a purposive selection method. The study on the situation of the elderly society in Khlong Kai Thuen Subdistrict, Khlong Hat District, Sa Kaeo Province, found that there are 811 elderly who are aged 60 years and over, which can be distinguished into groups according to their capabilities: the socially-active group, the homebody group, and the bedridden group. Such a situation tends to be increasing due to the poor economic situation affecting marriage and childbearing of the younger generations. As for factors related to possible improvement on the quality of life of the elderly, it is found that the most impactful factor is economics, followed by social security, societal factors, and education. For the elderly to have a good quality of life, having enough income for daily expenses and for treating chronic diseases is the utmost necessity. This research also found that there are several possible guidelines to help improve the quality of life of the elderly, such as through activities in the elderly schools that allow the offsprings of the elderly to participate in training or lecturing sessions regarding food and nutrition for the elderly, or organizing participatory care projects in different villages, collaborating with various agencies, and creating sustainable long-term caring networks that cover the whole sub-districts and effectively connect different agencies.